Ozone Layer Depletion: A Global Concern - Dube, Shiva Kant (Academic Voices: A Multidisciplinary Journal, 2018)
The distribution of ozone in the stratosphere is a function of altitude, latitude and season. It is determined by photochemical and transport processes. The ozone layer is located between 10 to 50 km above the earth’s surface and contains 90 percent of all stratospheric ozone. Under normal conditions, stratospheric ozone is formed by a photochemical reaction between oxygen molecules, oxygen atoms and solar radiation. The ozone layer is essential to life on earth, as it absorbs harmful ultraviolet-B radiation from the sun. In recent years the thickness of this layer has been decreasing, leading in extreme cases to holes in the layer. Measurements carried out in the Antarctic have shown that, more than 95 percent of the ozone concentrations found at altitudes between 15 to 20 km and more than 50 percent of total ozone are destroyed. The main cause of ozone layer depletion is the increased stratospheric concentration of chlorine from industrially produced CFCs i.e. chlorofluorocarbons. Thus, the effective implementation of commitments made in national conventions, international treaties and global cooperation would help to safeguard this protective shield and earth’s umbrella.